2022
DOI: 10.1177/08901171221104458
|View full text |Cite
|
Sign up to set email alerts
|

Physical Activity and Multimorbidity Among Community-Dwelling Older Adults: A Systematic Review With Meta-Analysis

Abstract: Objective This study evaluated the relationship between physical activity (PA) and multimorbidity in community-dwelling older adults. Data Source A systematic review and meta-analysis in the following databases: Pubmed, Lilacs, Scielo, Web of Science, Scopus, and AgeLine. Study inclusion and Exclusion Criteria It included observational studies investigating the association between physical activity and multimorbidity, with older adults, published until May 2021. Studies with institutionalized individuals or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…This controversy would require specific studies in order to be resolved. In our study, the data are in line with the results presented in the aforementioned meta-analysis ( 31 ), but no differentiation has been made between types of pathologies that cause pain or fatigue, so that our results could not enter into discussion with the aforementioned controversy.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…This controversy would require specific studies in order to be resolved. In our study, the data are in line with the results presented in the aforementioned meta-analysis ( 31 ), but no differentiation has been made between types of pathologies that cause pain or fatigue, so that our results could not enter into discussion with the aforementioned controversy.…”
Section: Discussionsupporting
confidence: 85%
“…Multimorbidity has been shown to be a variable that is inversely related to physical exercise. A meta-analysis studying the relationship between physical activity and multimorbidity showed that the probability of physical exercise in the older adult population with multimorbidity is OR = 0.81 (95% CI = 0.73–0.89) ( 31 ). This relationship has been controversial in the literature, since some authors identify morbidity associated with pathologies that cause pain or fatigue as a factor associated with lower adherence to physical activity ( 7 ) and other authors refute this idea by not identifying differences between people with cardiovascular disease or diabetes, which are not usually associated with pain or fatigue ( 32 ).…”
Section: Discussionmentioning
confidence: 99%
“…Older adults with lower levels of physical activity are more likely to suffer from multimorbidity. Christine et al [ 59 ] showed that there was an inverse association between physical activity and multimorbidity among seniors aged ≥65 years, and this association was easier to be found in studies that include more than ten chronic diseases [ 60 ]. At the family and social network layer, widowhood was a risk factor for multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 23 , 24 As a result, exercise improves functional status, independence, and QOL while decreasing multimorbidity, and polypharmacy. 21 , 25 , 26 Moreover, use of senolytics, drugs with the ability to clear senescent cells, mimic some of the properties of exercise and may therefore also reduce musculoskeletal decline associated with aging. 27 , 28 …”
Section: Be More Active (Exercise)mentioning
confidence: 99%